Computerised speech and language therapy can help people with aphasia find words following a stroke. (25th March 2020) - Cook, Rob; Davidson, Peter; Martin, Rosie
The study: Palmer R, Dimairo M, Cooper C, et al. Self-managed, computerised speech and language therapy for patients with chronic aphasia post-stroke compared with usual care or attention control (Big CACTUS): a multicentre, single-blinded, randomised controlled trial. Lancet Neurol 2019;18:821-33. This project was funded by the NIHR Health Technology Assessment Programme (project number 12/21/01) and the Tavistock Trust for Aphasia. To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000864/after-a-stroke-computerised-speech-and-language-therapy-can-help-people-find-words